Changes in basic soil properties and enzyme activities along an afforestation series on the dry Aral Sea Bed, Kazakhstan. Issue 1 (2nd January 2020) - An, Jiae; Chang, Hanna; Han, Seung Hyun; Khamzina, Asia; Son, Yowhan
Abstract: Afforestation of the desiccated Aral Sea Bed is needed for the rapid introduction of vegetation and rehabilitation of the soil environment. The present study aimed to detect the soil amelioration effect by afforestation of the Aral Sea Bed with respect of changes in topsoil properties and enzyme activities. In August and November 2018, soils were sampled from the barren areas and from areas afforested in 1991, 2005, 2009, 2010, and 2013. The exchangeable base cation concentrations (Ca 2+, K +, Mg 2+, and Na + ), cation exchange capacity (CEC), plant-available P concentration, electrical conductivity, pH, and enzyme activities (acid phosphatase, β-glucosidase, and N-acetyl-glucosaminidase) were analyzed in the surface soil (0–10 cm). Base cation concentrations, CEC, and electrical conductivity decreased following afforestation possibly because of root absorption. The observed increase in soil pH could be affected by both root absorption and decomposition of plant residues. Enzyme activities, which are early indicators of soil recovery, might have been increased by afforestation through the release of nutrients from litter and root exudates. Our findings indicate that the establishment of vegetation through afforestation can provide supportive microenvironments for plants and microorganisms by decreasing soil salinity and activating soil microbial enzymes; these effects of afforestation are amplified over time.